Peran Brand Image, Brand Trust Dan Kualitas Informasi Terhadap Keputusan Pembelian Di Tiktok Shop (Studi Kasus Remaja Kota Malang) - Zahrotul Nadiah; Nur Hidayati; Fahrurrozi Rahman (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to analyze the role of Brand Image, Brand Trust, and Information Quality on purchasing decisions at the tiktok shop for Malang City Youth. The sampling method used is maholtra. The population of this research is Malang City Teenagers and the number of samples is 64 respondents. The analysis used is multiple linear regression. The results of the study show that Brand Image and Brand Trust have no significant effect on Purchasing Decisions, while the Information Quality variable has a significant effect on Purchasing Decisions. Keywords: Brand Image, Brand Trust and Information Quality, Purchasing Decision